Feasibility study of two‐terminal tandem solar cells integrated with smart stack, areal current matching, and low concentration. (9th December 2016) - Baba, Masaaki; Makita, Kikuo; Mizuno, Hidenori; Takato, Hidetaka; Sugaya, Takeyoshi; Yamada, Noboru
Abstract: The "SMAC module" is a low‐cost, high‐efficiency photovoltaic module that integrates three techniques: a "SM art stack, " "A real current matching, " and "solarC oncentration." This paper presents the result of a proof‐of‐concept study of the SMAC module conducted using device simulations and indoor experiments. The simulation results show that an SMAC module with a two‐terminal GaAs/Si tandem solar cell can achieve an efficiency of approximately 30% and superior electricity generation per unit top cell area. The performance of the GaAs/Si solar cell developed in this study is similar to that of a GaAs/InGaAsP solar cell under concentrated artificial sunlight and is consistent with the simulation results. © 2016 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. Abstract : The "SMAC module" is a low‐cost, high‐efficiency photovoltaic module that integrates three techniques: a "SMart stack, " "Areal current matching, " and "solar Concentration." The result of a proof‐of‐concept study shows that an SMAC module with a two‐terminal GaAs/Si tandem solar cell can achieve an efficiency of approximately 30% and superior electricity generation per unit top cell area.